Modelling the responses of partially migratory metapopulations to changing seasonal migration rates: From theory to data. Issue 9 (17th July 2022) - Payo‐Payo, Ana; Acker, Paul; Bocedi, Greta; Travis, Justin M. J.; Burthe, Sarah J.; Harris, Michael P.; Wanless, Sarah; Newell, Mark; Daunt, Francis; Reid, Jane M.
Abstract: Among‐individual and within‐individual variation in expression of seasonal migration versus residence is widespread in nature and could substantially affect the dynamics of partially migratory metapopulations inhabiting seasonally and spatially structured environments. However, such variation has rarely been explicitly incorporated into metapopulation dynamic models for partially migratory systems. We, therefore, lack general frameworks that can identify how variable seasonal movements, and associated season‐ and location‐specific vital rates, can control system persistence. We constructed a novel conceptual framework that captures full‐annual‐cycle dynamics and key dimensions of metapopulation structure for partially migratory species inhabiting seasonal environments. We conceptualize among‐individual variation in seasonal migration as two variable vital rates: seasonal movement probability and associated movement survival probability. We conceptualize three levels of within‐individual variation (i.e. plasticity), representing seasonal or annual variation in seasonal migration or lifelong fixed strategies. We formulate these concepts as a general matrix model, which is customizable for diverse life‐histories and seasonal landscapes. To illustrate how variable seasonal migration can affect metapopulation growth rate, demographic structure and vital rate elasticities, we parameterize our general models for hypothetical short‐ and longer‐lived species. Analyses illustrate that elasticities of seasonal movement probability and associated survival probability can sometimes equal or exceed those of vital rates typically understood to substantially influence metapopulation dynamics (i.e. seasonal survival probability or fecundity), that elasticities can vary non‐linearly, and that metapopulation outcomes depend on the level of within‐individual plasticity. We illustrate how our general framework can be applied to evaluate the consequences of variable and changing seasonal movement probability by parameterizing our models for a real partially migratory metapopulation of European shags Gulosus aristotelis assuming lifelong fixed strategies. Given observed conditions, metapopulation growth rate was most elastic to breeding season adult survival of the resident fraction in the dominant population. However, given doubled seasonal movement probability, variation in survival during movement would become the primary driver of metapopulation dynamics. Our general conceptual and matrix model frameworks, and illustrative analyses, thereby highlight complex ways in which structured variation in seasonal migration can influence dynamics of partially migratory metapopulations, and pave the way for diverse future theoretical and empirical advances. Abstract : The authors provide a novel conceptual framework that explicitly incorporates seasonal movement probability, and associated survival, as metapopulation‐level vital rates, and within‐individual variation in seasonal movement (i.e. plasticity). They illustrate how movement vital rates and plasticity can interact to shape the dynamics and persistence of partially migratory metapopulations across different life‐histories.